Analisis Faktor Risiko Kejadian Hipertensi Di Wilayah Kerja Puskesmas Rarowatu Utara Kab. Bombana Tahun 2011 - Saida Saida (STIKes Karya Kesehatan, 2014)
The prevalence of hypertensive disease in Indonesia isestimate daround 11.8%-28. 6% of the populationaged >20 years have hypertension. This study aims to analyze the risk factors that could affect the occurrence of hypertension in the working area Rarowatu HealthCenterNorthin2011.This type of observational analytic study with case control study design. Accidental sampling with sampling, sample 68 cases of people with hypertension and control 68 people instead of people with hypertension a5%.Data were analyzed with bivariate tests and multivariat logistic regression test with Bivariate results showed a family history of risk OR = 2.30 (95% CI 1.05 to 5.04), salt consumption OR = 19.8 (95% CI 8.34 to 47.85), cigarette smoking with OR = 5.73 (95% CI 2.28 to 4.41), less physical activity OR = 6.66 (95% CI 2.77 to 16.04), obesity OR = 3.56 (95% CI 2, 77 to 6.04), stress OR = 13.89 (95% CI 5.28 to 36.51) has a meaningful relationship, alcohol consumption OR = 2.88 (95% 0.73 to 11.39), has non-significant relationship with Genesis Hipertansi in the Work Area Health Center Rarowatu Year 2011. Multivariat test results indicate risk factors that most impact on the incidence of hypertension is salt consumptionOR=15.907. Family history factors, salt intake, smoking habits, physical activity is lacking, obesity, stress associated with the incidence of hypertension, alcohol consumption is not associated with incident hypertension. Advice, the need to avoid foods high in sodium, avoid smoking, avoid stress, avoid obesity, do physicalactivity every day, regular blood pressure control. Keywords: Genesis hypertension, family history, salt consumption, smoking habits, alcohol consumption, less physical activity, obesity, stress